2018
DOI: 10.1021/acs.cgd.8b00878
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Pyrazinamide Eutectics versus Cocrystals Based on Supramolecular Synthon Variations

Abstract: Cocrystallization of the antituberculosis drug pyrazinamide (PZA) with several substituted aromatic carboxylic acids as coformers was studied. The combinations were analyzed by X-ray diffraction and melting behavior to assess the formation of eutectic versus cocrystal. Benzoic acid, cinnamic acid, and N-heterocycle coformers gave eutectics, whereas the majority of their hydroxyl/methoxy substitutes formed cocrystals with PZA. X-ray crystal structures were obtained for some cocrystals, and binary phase diagrams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 51 publications
(75 reference statements)
0
23
0
Order By: Relevance
“…Several polymorphs of cocrystals of PZA with succinic acid (Cherukuvada and Nangia, 2012;Luo and Sun, 2013), malonic acid (Kulla et al, 2017) and theophylline (Eddleston et al, 2015) have been found and investigated. Different binary mixtures leading to either cocrystals or eutectic systems have been described by Rajbongshi et al (Rajbongshi et al, 2018). A ternary cocrystal has been designed by using a "drug-bridge-drug" strategy involving PZA combined with another first-line antitubercular drug isoniazid using fumaric acid as the bridge (Liu et al, 2018).…”
Section: Literature Data On the Phase Behavior Of Pyrazinamidementioning
confidence: 99%
“…Several polymorphs of cocrystals of PZA with succinic acid (Cherukuvada and Nangia, 2012;Luo and Sun, 2013), malonic acid (Kulla et al, 2017) and theophylline (Eddleston et al, 2015) have been found and investigated. Different binary mixtures leading to either cocrystals or eutectic systems have been described by Rajbongshi et al (Rajbongshi et al, 2018). A ternary cocrystal has been designed by using a "drug-bridge-drug" strategy involving PZA combined with another first-line antitubercular drug isoniazid using fumaric acid as the bridge (Liu et al, 2018).…”
Section: Literature Data On the Phase Behavior Of Pyrazinamidementioning
confidence: 99%
“…If the adhesive interactions dominating the resulting compound are characterized as a cocrystal, and yet if both interactions, adhesive and cohesive, are balanced and a match of size/shape between the components occurs, a solid solution is formed [39]. Furthermore, Rajbongshi et al also studied the formation of eutectics through crystallization processes with pyrazinamide and different aromatic carboxylic acids characterized by a "V" shape phase diagram [40].…”
Section: Thedes For Tuberculosis Treatmentmentioning
confidence: 99%
“…In order to understand the formation of eutectics as opposed to cocrystals for selected combinations, we have performed supramolecular synthon energy calculations similar to our previous work. [5] Specifically, we extracted clusters of molecules from the published structures of ETZ-FRA and ETZ-SA cocrystals (Figure 8) and computed the intermolecular interaction energy using DFT. Subsequently, hypothetical clusters corresponding to ETZ-CA and ETZ-BA adducts were generated by replacing the hydroxyl group with hydrogen atoms in FRA and SA molecules, respectively.…”
Section: Supramolecular Synthon Energy Calculationsmentioning
confidence: 99%